Optimalisasi Perbaikan Kualitas Produksi Donat Menggunakan Quality Control Circle (QCC) - Sofiyanurriyanti, Sofiyanurriyanti; Adib, Adib; Kasmawati, Kasmawati; Irawan, Heri Tri; Akmal, Abdiel Khaleil; Danil, Danil (Universitas Teuku Umar, 2025)
Donuts are one of the most popular foods in the community that have a sweet, savory, and unique taste. One of the donut branches in this study is located in Drien Rampak Village, Johan Pahlawan, West Aceh Regency. This study used the Quality Control Circle (QCC) method with the PDCA (Plan, Do, Check, Action) and 5W + 1H approaches. The data analyzed included product defects during the period June 2023 to May 2024, which included burnt color, inappropriate size, flat, and not rising. The results showed that the average defect rate reached 6% of the total monthly production. By implementing the QCC method, the main causes of defects were successfully identified using tools such as Pareto diagrams, cause-and-effect diagrams, and control charts. Improvement steps include implementing SOPs, employee training, and quality control at critical stages of production. The implementation of this method succeeded in significantly reducing the level of product defects, increasing production efficiency, and improving consumer satisfaction. This study provides a practical contribution to companies in controlling product quality and is a reference for further research related to quality management using the QCC method.